The Meaning and Value of Kia Lahi Traditional Rituals in the Tidore Community - Abd. Chaidir Marasabessy (Yayasan Keluarga Guru Mandiri, 2025)
The Kia Lahi ritual tradition is not merely a union of two individuals; it embodies the cultural, spiritual, and social values passed down from ancestors. This study describes the process of the Kia Lahi ritual and analyzes the meanings and values inherent within it. A phenomenological approach is employed, utilizing interviews as a data collection technique, supplemented by a review of relevant literature. Data analysis involves classifying information according to established formulas. The data is processed by referencing various sources, interpreting findings, and drawing conclusions to comprehend the meanings and values within the Kia Lahi ritual. The Kia Lahi ritual of the Tidore people consists of 17 stages. This ritual signifies kinship, respect, purity, reverence, and devotion to one's faith. Additionally, it conveys the concept of